Physical and Mental Health Effects of Characteristics of Caregivers and the Caregiving Situation - Son, Chong-Hwan (Archives of Business Research, 2021)
The present study investigated the effects of characteristics of caregivers and the caregiving situation on family caregivers’ physical/mental health, using the multiple regression analysis with the time-series and cross-sectional data from the 2015-2018 Behavioral Risk Factor Surveillance System (BRFSS). The regression results indicated that the caregiving role could increase the risk of developing physical/mental health problems. Importantly, this study revealed that the characteristics of caregivers and care recipients were significantly associated with caregivers’ physical/mental health outcomes. Especially the results showed that the caregiver support program was the most significant factor linked to caregivers’ physical/mental health. It pointed to the importance of caregiver education and support programs for family caregivers to cope with the stress from providing care or daily assistance. The results also pinpointed which area of support services for informal caregivers would be a priority to enhance. Thus, the public health policymakers should re-evaluate the current long-term care program to establish a more effective caregiving structure, especially caregiver education and support programs for family caregivers, to improve the informal caregivers’ quality of life.